2019
DOI: 10.1111/1756-185x.13652
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of uric acid‐lowering therapy on hypercholesterolemia and hypertriglyceridemia in gouty patients

Abstract: Aim:To investigate the effects on hypercholesterolemia and hypertriglyceridemia in gouty patients receiving uric acid-lowering therapy (UALT). Methods:A retrospective study was performed from January 2015 to December 2017 in gouty patients receiving UALT. A total of 124 gouty patients with hypercholesterolemia or hypertriglyceridemia who were administered UALT were monitored.Of the 124 patients with gout, 52 were treated with febuxostat, 29 were treated with allopurinol, and 43 were treated with benzbromarone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
5
9
0
Order By: Relevance
“…It is consistent with a longitudinal study in China that found that the highest quartile of SUA had 45.6% of cumulative incidence to hypertriglyceridemia [31]. In this sense, Jing Wu et al showed that uric acid-lowering therapy effectively improved serum cholesterol and triglyceride levels up to 80 mg/dL [32]. is may be explained by early metabolic changes such as activation of mitochondrial NADPH oxidase and inhibition of AMPK and AKT2, which alter lipid metabolism, mainly triglycerides [9].…”
Section: Discussionsupporting
confidence: 81%
“…It is consistent with a longitudinal study in China that found that the highest quartile of SUA had 45.6% of cumulative incidence to hypertriglyceridemia [31]. In this sense, Jing Wu et al showed that uric acid-lowering therapy effectively improved serum cholesterol and triglyceride levels up to 80 mg/dL [32]. is may be explained by early metabolic changes such as activation of mitochondrial NADPH oxidase and inhibition of AMPK and AKT2, which alter lipid metabolism, mainly triglycerides [9].…”
Section: Discussionsupporting
confidence: 81%
“…Differences in race and ethnicity and baseline BMI could explain the heterogeneity of the results. Moreover, effects of ULT on blood triglycerides and cholesterol have been inconclusive both in animal experiments and clinical studies [ 21 , 48 50 ]. Given the complexity of lipid metabolism, measuring triglycerides and cholesterol may not be able to capture subtle differences or the effect of ULT on specific classes of lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Xanthine oxidase inhibitor (XOI) therapy, particularly by use of allopurinol and febuxostat, is the primary approach used to treat hyperuricemia and thereby lower body urate stores [ 18 ]. XOI has had favorable treatment effects on experimental small animal models of hypertension, renal disease progression, atherosclerosis, and NASH [ 16 , 19 , 20 ], though net effects of XOI-based urate-lowering therapy remain unclear in adult humans with these conditions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result can be explained by the fact that fasting glucose was positively correlated to SU when it is below the threshold (6.5 mmol/L in men and 7.5 mmol/L in women) ( 33 ). In addition, the indirect mechanism of insulin resistance may also be involved in the results ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%